Bernard Shaw as a Poetic Dramatist - Stow, Mary Glenys (My University, 1967)
This thesis attempts to define Shaw's meaning for the terms "poet" and "poetry" as they appear in his prose works, and to compare that meaning with the usage of modern criticism. It examines in the light of these definitions some passages selected from Shaw's plays, pointing out the oracular and often Biblical nature of their rhythm and imagery, and making a distinction between those speeches which are rhetorical or persuasive and those which are poetic or introspective. It then explores in detail the rhythmic dialogue and symbolic significance of three dramas, Major Barbara, Heartbreak House, and Saint Joan, contending that the creative ability which is present in these plays may reasonably be called poetic.
Keywords: English; English Language and Literature; English Language and Literature